The ethnobotany of benzoin (Styrax spp.) - Y. Purwanto; E.B. Walujo; Esti Munawaroh (Journal of Tropical Ethnobiology, 2005)
This article deals with the observations made in a field research in a Barak Toba, North Tapanuli, North Sumatra, concerning the traditional agricultural rem and the ethnobotany of benzoin. The society of North Tapanuli classify three kinds of benzoin tree according to the quality of the resin, i.e., hamijon toba, ham.rjon durame and lranlijon bole. Ilarnijon toba is identified as Sri-ras paralloloncurem Perk., which is cultivated at locations above 1000 in contour and produce the best quality resin. HArnijon durarne which is cultivated at lower elevation site 500-1000 try., produces a lower quality material. It can be identified as StsTax benzoin Dryand. And for the harnijon bubo has not been exactly identified, but concerning the morphology and habitat of the tree and the characters of its resin seem to suggest that it may be a kind of natural hybrid of the two species referred to above., The resin can be obtained from the trees of 6-70 years of age. The quality of the resin is primarily determined by the species of benzoin tree. The older the trees. however, the lesser the amount of high grade resins. The commercial blend-benzoms are manufactured by blending different quality resins in various proportions. Even the daminar, a non benzoin material, is mixed to fairly high percentages.